Cross-Border Cooperation and Intelligence Sharing in Combating Transnational Crimes in ECOWAS Region - Egbeaduma, Julius Egbeaduma; Idowu, Olusegun; Fasuan, Olawale (African Journal of Stability and Development (AJSD), 2025)
Transnational crimes, such as human trafficking, arms smuggling, terrorism, drug trafficking, and cybercrime, continue to threaten the stability and development of the Economic Community of West African States (ECOWAS). Porous borders, weak institutions, and limited intelligence-sharing mechanisms hinder the collective security efforts of ECOWAS’s fifteen member states. This study investigates the role of cross-border cooperation and intelligence sharing in combating these transnational crimes. It critically examines existing regional frameworks, evaluates their effectiveness, and explores the structural and operational challenges undermining cooperation among member states. The findings underscore the necessity of enhanced coordination, trust-building, and technological investment to strengthen regional security architecture and disrupt criminal networks. The study contributes to understanding how integrated intelligence efforts can fortify West Africa’s response to complex security threats.